ANALYSIS OF Cr, Cu AND Zn IN SOFT TISSUE OF DIFFERENT SIZES OF KEPAH (Meretrix meretrix) FROM PANTAI CERMIN COASTAL WATERS, NORTH SUMATRA - Azhara Diana; Bintal Amin; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in April 2018 by taking samples of Kepah (M. meretrix) in Pantai Cermin coastal waters,North Sumatra Province. The aim of this research was to determine metal content (Cr, Cu and Zn) in the soft tissue of kepah (M. meretrix)based on size and different stations, to evaluate the relationship of heavy metals content in soft tissueof kepah with size and to estimate the safety limit of the consumption of kepah. The highest concentration of Cr and Cufound in medium sizes at station 3 (5.683 µg/g and 2.517 µg/g). The highest content of Zn also found in medium sizes but at station 1 (88.333 µg/g). A possitiverelationship between Cr, Cu, and Zn in the soft tissue of the shellfishwith its size was identified.The safe limit of consuming Kepah shellfish from the studied area based on the value of PTWI for Cr, Cu and Zn are1,973,663,49and 46,035 kg/week respectively.Key words: Heavy metals, Pollution, North Sumatra, M. meretrix